PENCIPTAAN KARYA SENI RUPA ABSTRAKSI WAJAH TOGOG DAN TOPENG BUJANG GANONG DENGAN TEKNIK CBT (CETAK BENANG TARIK) - Zarkasi, Sofwan; Suwasono, Bening tri (Acintya, 2019)
ABSTRACT”Penciptaan Karya Seni Rupa Abstraksi Wajah Togog Dan Topeng Bujang Ganong Dengan Teknik CBT (Cetak Benang Tarik)”( The Creation Of Abstraction Artworks Of Togog’s Face And The Mask Of Bujang Ganong With CBT (Print Thread) Technique) by Sofwan Zarkasi and Bening Tri Suwasono is based on the opportunities related to creativity and experimentation in two-dimensional works of art that utilize systems or techniques of creation in graphic arts, which have two-dimensional print art characters. One of them is creating mono print graphic artwork with a print process that utilizes tensile threads, namely threads that are colored and printed on paper and pulled with a little pressure. This research aims to open wide opportunities for creativity in two-dimensional works of art. The method applied in the creation of works in this study is using the theoretical approach of L. Chapman, which mentions three stages. The first stage is finding ideas by approaching the source of inspiration; the second stage includes refinement, development and establishment of the initial idea, including how the artist perfects, develops and establishes the initial idea which in this case relates to the search of forms, the choice of medium, tools, materials, and techniques; and the third stage, visualization into media, namely how artists visualize in the media. Indirectly the theory also put forward the experimentation, which in this study is the technique of Tensile Print (CBT) which produces the image prints in the form of lines that form the visual subject of Togog’s face and Bujang Ganong’s face mask in two-dimensional media. The results of this aristic research are two-dimensional works of art in the form of abstractions of Bujang Ganong masks with the characteristics of printed characters from the attraction of colored threads.From the creation of abstraction artworks of Togog’s face and the mask of Bujang Ganong with CBT (Print Thread) technique, this two-dimensional art works with the traditional dimensions is expected to be rich of innovation, both in technique and form, so that it can raise the prestige of the arts.Keywords: Fine Arts, two dimensions, abstraction, puppets, CBT.